2020
DOI: 10.1177/0091217420913388
|View full text |Cite
|
Sign up to set email alerts
|

Burden, quality of life, anxiety, and depressive symptoms among caregivers of hemodialysis patients: The role of social support

Abstract: Objective The purpose of this study was to determine how burden and quality of life predict anxiety and depressive symptoms among caregivers of hemodialysis patients. Social support was included in the model as a proposed moderator in the above relationships. Methods This cross-sectional study involved 340 caregivers of chronic kidney patients undergoing hemodialysis. The setting was in Terengganu, Malaysia. The caregivers completed the measures of caregiving burden, quality of life, social support, and sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
(42 reference statements)
2
14
0
2
Order By: Relevance
“…Caregivers neglect their health and do not engage in leisure activities, leading to a deterioration in their quality of life. A previous study found that caregivers caring for HD patients developed various physical health problems [ 33 ], indicating a deterioration in the quality of life of caregivers; this finding has been supported by the previous studies [ 34 ]. Based on these problems, we need to recognize the need for caregivers’ independent lives; numerous efforts will be needed to enable caregivers to live their own lives.…”
Section: Discussionsupporting
confidence: 68%
“…Caregivers neglect their health and do not engage in leisure activities, leading to a deterioration in their quality of life. A previous study found that caregivers caring for HD patients developed various physical health problems [ 33 ], indicating a deterioration in the quality of life of caregivers; this finding has been supported by the previous studies [ 34 ]. Based on these problems, we need to recognize the need for caregivers’ independent lives; numerous efforts will be needed to enable caregivers to live their own lives.…”
Section: Discussionsupporting
confidence: 68%
“…Regarding depression, our study found that 86.4% of caregivers had low depression. Several studies show that caregivers of patients have high percentages of mild to moderate depression [ 39 , 40 ]. In addition, the study found that the higher the level of depression, the poorer the caregiver’s quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Social support is often considered a protective factor in reducing caregiver burden and improving their quality of life. 14 Existing research points out that fewer caregivers of COPD patients perceive adequate social support and that their level of social support utilization is not high. 15 Perceived social support refers to the degree to which individuals perceive the evaluation and expectations of the full range of social support they receive.…”
Section: Introductionmentioning
confidence: 99%
“…18 Perceived social support is also effective in negatively predicting caregiver burden. 14 It has also been suggested that the level of social support is an important predictor of caregiver quality of life, and the higher the level of perceived social support, the higher the level of quality of life of the individual. 19 Caregivers who respond negatively when providing care to patients may create a vicious cycle effect with their poor mental health status.…”
Section: Introductionmentioning
confidence: 99%